Sistem Pendeteksi Suhu dan Asap Pada Ruangan Tertutup Memanfaatkan Sensor LM35 Dan Sensor AF30 - Usuman, Ilona; Aardhi, Hasmi (BERKALA FISIKA, 2010)
As is known together for this cause of the fire is very varied, ranging from natural factors, or electrical short circuit can occur because of the element of intent. Due to these reasons, so it is necessary to have a system that can detect early occurrence of fire. Fire monitoring system must be able to accommodate the nature of the fire.By leveraging the LM35 sensor that functions observed rise in temperature and observing the presence of smoke sensors AF30 can be created around the smoke detector and temperature using LM35 sensor and microcontroller AT89S51 AF30 sensor and equipped with facilities to send sms if there is any indication of a hazard or fire will occur. The results show that the system could work well in the prototype room with a distance of heat source and smoke source ± 5cm from the two sensors, when the system detects hot and smoke, the water pump, buzzer and fan that is connected to a relay works, then sms will be sent to the user. The temperature sensor detects the heat from 25 degrees to 60 degrees, while the temperature is 55 degrees is considered dangerous. Sensors detect smoke cloud of smoke from 30 to 125 mvolt mvolt, cloud of smoke which is considered the danger is over 125 mvolt. Keywords: Fire, LM35 temperature sensor, smoke sensor AF30, Short Message Service (SMS)